Analyse spatiale des crimes commis sur la rue à l’intérieur des marchés de drogues - Weisburd, David; Green, Lorraine; Ross, Debra (Criminologie, 1994)
In this paper we utilize data from the Drug Market Analysis Program (DMAP) in Jersey City, New Jersey, to provide some preliminary insight into the spatial relationship between street level drug markets and crime. We begin our paper with a description of how the DMAP information system was used to define drug markets and the characteristics of the markets that were identified. We then turn to an analysis of the incidence of reported crime within drug market boundaries. We find that drug market areas include a disproportionate share of arrests and crime related emergency calls for service in Jersey City. Streets and intersections within the drug markets are also much more likely to evidence reported crime than non-drug market places. We conclude with a discussion of our findings and the implications of our research for further study of the spatial relationships between drug markets and crime.